2005
DOI: 10.1289/ehp.7712
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Blood and Brain Mercury Levels in Infant Monkeys Exposed to Methylmercury or Vaccines Containing Thimerosal

Abstract: Thimerosal is a preservative that has been used in manufacturing vaccines since the 1930s. Reports have indicated that infants can receive ethylmercury (in the form of thimerosal) at or above the U.S. Environmental Protection Agency guidelines for methylmercury exposure, depending on the exact vaccinations, schedule, and size of the infant. In this study we compared the systemic disposition and brain distribution of total and inorganic mercury in infant monkeys after thimerosal exposure with those exposed to M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
172
0
4

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 207 publications
(188 citation statements)
references
References 31 publications
(56 reference statements)
12
172
0
4
Order By: Relevance
“…61 Despite its short half-life compared to inorganic mercury, it undergoes preferential accumulation in the CNS, affecting the microglia and producing strain-dependent neurotoxic effects in rodents. 62,63 This strain dependency, in conjunction with the present data, suggests that thimerosal could contribute to produce an unbalanced Ca 2 þ homeostasis in genetically vulnerable individuals. Indeed, a postnatal exposure to thimerosal is not reconcilable with the prenatal onset of neurodevelopmental anomalies leading to autism.…”
Section: à1688supporting
confidence: 71%
“…61 Despite its short half-life compared to inorganic mercury, it undergoes preferential accumulation in the CNS, affecting the microglia and producing strain-dependent neurotoxic effects in rodents. 62,63 This strain dependency, in conjunction with the present data, suggests that thimerosal could contribute to produce an unbalanced Ca 2 þ homeostasis in genetically vulnerable individuals. Indeed, a postnatal exposure to thimerosal is not reconcilable with the prenatal onset of neurodevelopmental anomalies leading to autism.…”
Section: à1688supporting
confidence: 71%
“…Carneiro et al demonstrated a conversion of ethylmercury to inorganic mercury in murine brain tissue within 6 days after exposure to thiomersal. 12 The dealkylation of MeHgCl seems not to be as effective as after thiomersal application as reported by Burbacher et al 13 However, we could show clear differences between organic and inorganic compounds in the efflux behaviour across the cell culture model of the blood-CSF barrier indicating compounds differences.…”
Section: Discussionsupporting
confidence: 43%
“…27 An in vivo study comparing Hg blood levels two days after oral MeHg intake (20 mg kg À1 as MeHg hydroxide) and intramuscular thiomersal injection (20 mg kg À1 ) in infant monkeys demonstrated total blood Hg concentrations of 8-18 ng mL À1 (0.04-0.09 mM) and of 6-14 ng L À1 (0.03-0.07 mM), respectively. 13 The application in the blood facing compartment lead to similar transfer rates for all mercury compounds (Fig. 5A-C).…”
Section: Transfer Across the In Vitro Model Of The Blood-csf Barriermentioning
confidence: 76%
See 1 more Smart Citation
“…Vahter et al [103] demonstrated that it was the ionic form of mercury (demethylated MeHg) that was most toxic and that it gradually accumulated in the brain over an 18 month period. Of special importance when comparing ethylmercury (EtHg) with MeHg brain toxicity, is that even though EtHg brain levels were 3-fold lower than MeHg, 34% of the EtHg was converted to the more toxic ionic form of mercury and only 7% of MeHg was converted in a similar time frame [104,105].…”
Section: Systemic Immune Activation and Microglial Primingmentioning
confidence: 99%